The role of regulator Eha in Edwardsiella tarda pathogenesis and virulence gene transcription. (June 2016) - Gao, Daqing; Li, Yuhong; Xu, Zeyan; Sheng, Ankang; Zheng, Enjin; Shao, Zeye; Liu, Nian; Lu, Chengping
Abstract: Edwardsiella tarda is a pathogen with a broad host range that infects both animals and humans. Eha is a new transcriptional regulator identified in ET13, which is involved in the bacterial hemolytic activity. This study explored the effect of the Eha in the pathogenesis of E. tarda and the transcriptional regulation of the bacterial virulence genes ( eseC, fliC, pagC and fim A). Our results found that the virulence of the eha mutant was 2.5-fold less than the one of its wild ET13 by LD50 in a murine model of i.p. infection, and the bacterial loads of the mutant displayed a different profile from the one of the wild strain. Most significantly, the mice infected with the mutant have greatly reduced acute inflammation in the liver, spleen and kidney compared to the ones infected with the wild. We further demonstrated that eseC, fliC and pagC were regulated directly by the Eha with qRT-PCR and β-Galactosidase assay, but fim A wasn't done. The promoter regions of the genes modulated and the cly gene reported before had been found to contain a common conserved motif by using software. In addition, we found that the wild strain was more toxic to RAW264.7 macrophages, and induced less the host cell apoptotic responses than the eha mutant did. Altogether, these data suggested that the Eha was required for the bacterial infection and the transcriptive regulation of the important virulence genes of E. tarda . Graphical abstract: Highlights: The eha mutant were attenuated by LD50. The bacterial loads of the mutant displayed a different profile from the one of the wild strain. The tissues infected with the wild strains showed the most extensive inflammation, but the mutant infection was a lack of the histopathological alterations. The eha gene can activate directly eseC, fli C and pag C. The wild strain was more toxic to macrophages, and induced less the host apoptotic responses than the mutant did.